Organizational Learning in Schools: The Antecedent and Moderating Factors - Rosheedat Adeniji (Canadian Journal for New Scholars in Education)
This review paper explores 20 peer-reviewed articles on the concept of organizational learning in schools between 2015 and 2023. Using qualitative systematic analysis method to synthesize and analyze current research literature, the study identified various ways in which scholars have described organizational learning, the conditions that precede and moderate organizational learning in schools. The findings established that school culture, school climate, leadership styles, shared leadership, and teacher leadership are antecedent factors that enact organizational learning while teacher collaboration, principal’s innovative behavior, professional learning community, and departmental leadership are found to moderate the effects of organizational learning. The study provides implications for research and practice on creating and maintaining a school culture that encourages effective organizational learning that productively responds to the continuous and dynamic initiatives in school environment in today’s complex world.